GDRP AND Inflation as Predictors For Profitability Ratios (A Case Study For Local Governments In Indonesia) - Kuntaryanto, Oki (Kiat Bisnis, 2013)
After the fall of Soehartoâs regime, Indonesia begins to endorse reformation on every sector. One of the important thing is to eradicate the country from corruption. Corruption can be prevented by endorsing a system, which encourage transparency and accountability. By the issuanceÂ of Government Rule No. 24 Year 2005 about Governmental Accounting, the transparency and accountability are facilitated within the rule. This research tries to investigate the influence of GDRP and inflation on profitability of local governments in Indonesia. This research is exploratory in nature due to the rareness of similiar researches. This research employs data from local governmentsâ audited financial statements in Indonesia. By using judgmental sampling, financial statements which the opinions are disclaimer and adverse are excluded from the analysis. The data analysis then conducted using ordinary least square. This research finds that both GDRP and inflation have influence on profitability ratios. For the future researches, the finding from this research can be extended using other ratios. Â Keywords: GDRP, Inflation, Local Governments, Profitability Ratios